A9.7 Cholesterol crystals induce neutrophil extracellular traps formation. (31st January 2014) - Jeremic, Ivica; Schorn, Christine; Munoz, Luis; Terzic, Tatjana; Schett, Georg; Herrmann, Martin
Abstract : Background and Objectives: Besides phagocytosis as mechanism to combat pathogens, neutrophils are able to eject DNA decorated with microbicidal proteins (neutrophil extracellular traps-NETs), that can immobilize and kill microorganisms extracellularly. Procoagulative properties of NETs have already been shown, however, a role of NETs formation in atherosclerotic disease has not been described so far. The process of chromatin release is referred to as NETosis. The aim of this study was to assess if cholesterol crystals are able to induce NETosis in vivo and in vitro . Materials and Methods: Polymorphonuclear cells-PMNs were isolated from blood obtained from healthy volunteers after informed consent. Isolated PMNs as well as whole blood were co/cultured with cholesterol crystals. After the treatment, cytospins were prepared and stained for DNA and neutrophil elastase. Extracelullar DNA was quantified by fluorometry. For in vivo experiments, cholesterol crystals were injected into murine air pouches. After 24h, air pouches were lavaged with PBS. After centrifugation cells were used for cytospins and supernatants for cytokines determination. Tophus-like aggregates were isolated and characterised by immune histochemistry and immunobloting. In addition, human autopsy specimens obtained from subject died of cardiac diseases were assessed for presence of NET markers. Results: Cholesterol induced dose dependent NETosis in isolated PMNs as well as in whole blood samples. The maximal applied concentration of cholesterol crystals induced 236.5% higher DNA release when compared to control. Cholesterol crystal injected in air pouches induced tophus-like aggregates composed of aggregated NETs attached to the cholesterol crystals. These structures were highly positive for citrullinated histones, markers of NET formation. NET markers were also found in atherosclerotic blood vessels in zones surrounding necrotic core of atheromatous plaque, which is rich in cholesterol crystals Discussion: This study showed for the first time ability of cholesterol crystals to induce NETosis in vitro, as well as in vivo . These data may explain prompt thrombus formation in atherosclerotic disease after rupture of fibrous cap of an atheromatous plaque containing huge amount of cholesterol crystals, which will be the subject of our future research.